My other two daughters - Surjit Singh Barnala; BARNALA (Surjit Singh) (New Delhi Vetri Publishers, 2008)
Surjit Singh Barnala, b. 1925, former chief minister of Punjab and governor of Tamil Nadu, India.
Keywords: Biography; Father and daughters; Politicians